2016
DOI: 10.1080/09540121.2016.1201194
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety were low amongst virally suppressed, long-term treated HIV-infected individuals enrolled in a public sector antiretroviral program in Thailand

Abstract: HIV/AIDS and anxiety/depression are interlinked. HIV-infected patients suffering from depression may be at risk for poor adherence which may contribute to HIV disease progression. Additionally, an HIV diagnosis and/or using certain antiretroviral agents may trigger symptoms of anxiety/depression. The objective of the study was to assess the prevalence and factors associated with anxiety and depression in HIV-infected patients from the Thai National HIV Treatment Program. This cross-sectional study was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 60 publications
3
24
0
Order By: Relevance
“…Contrary to our expectations, this study showed that no significant difference was observed in anxiety scores of PLWHAs and healthy individuals. Although this result differs from some published studies which reported that anxiety was higher in PLWHAs as opposed to general population (1-3, 6, 14, 49), it is consistent with other studies such as Prasithsirikul et al (2017) and Sewell et al (2000) (28,52).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Contrary to our expectations, this study showed that no significant difference was observed in anxiety scores of PLWHAs and healthy individuals. Although this result differs from some published studies which reported that anxiety was higher in PLWHAs as opposed to general population (1-3, 6, 14, 49), it is consistent with other studies such as Prasithsirikul et al (2017) and Sewell et al (2000) (28,52).…”
Section: Discussionsupporting
confidence: 77%
“…These contradictions in the results could be attributed to a variety of populations and instruments applied in different studies to ascertain the diagnosis of psychological disorders. One possible explanation for our findings might be that the mean duration of living with HIV in our sample was 5.52 ± 3.43 which is somehow a lengthy period in which PLWHAs have acquired skills to adapt to living with HIV so that they may no longer be afraid of dying from HIV (28,52).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Low awareness, lack of mental health policy, and lower health service utilization were accounted as the main barriers for mental health service in the country (7). This issue has drawn tremendous public health attention for the last ve years and there has been a wide-ranging interest to generate evidence on the comorbidity of depression and HIV (8)(9)(10)(11). However, very limited studies do exist and an increasing concern in resource-limited developing countries of the world where people living with HIV do not get an early mental health screening (12), awareness and linking to mental health service to the same level in developed countries, and the impact on daily life is still growing (13).…”
Section: Introductionmentioning
confidence: 99%
“…This issue has drawn a tremendous public health attention for the last ve years and there has been wide-ranging interest on the need to generate evidence on the subject matter related to the comorbidity of depression and HIV (8)(9)(10)(11). However, very limited studies do exist and an increasing concern in resourcelimited developing countries of the world where people living with HIV do not get an early mental health screening (12), awareness and linking to mental health service to the same level in developed countries, and the impact on daily life is still growing (13).…”
Section: Introductionmentioning
confidence: 99%